2012
DOI: 10.1155/2012/379215
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Different Behavior Modification Strategies Designed to Reduce Sedentary Screen Behaviors in Children

Abstract: Previous research suggests that reducing sedentary screen behaviors may be a strategy for preventing and treating obesity in children. This systematic review describes strategies used in interventions designed to either solely target sedentary screen behaviors or multiple health behaviors, including sedentary screen behaviors. Eighteen studies were included in this paper; eight targeting sedentary screen behaviors only, and ten targeting multiple health behaviors. All studies used behavior modification strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 68 publications
0
31
0
1
Order By: Relevance
“…Some studies measured sedentary behaviour in terms of recreational screen time (television viewing, watching videos/DVDs) and did not include educational activities such as doing homework or reading14 16 18 20 21; other studies included listening to music, reading, sitting around doing nothing or talking on the phone15 19; some studies did not clearly define sedentary behaviour 12 13 17…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies measured sedentary behaviour in terms of recreational screen time (television viewing, watching videos/DVDs) and did not include educational activities such as doing homework or reading14 16 18 20 21; other studies included listening to music, reading, sitting around doing nothing or talking on the phone15 19; some studies did not clearly define sedentary behaviour 12 13 17…”
Section: Resultsmentioning
confidence: 99%
“…Six reviews reported data on gender 13–15 18 19 21. While two reviews reported differential effects of the intervention between genders, such results were inconsistent across reviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33,35,36,[40][41][42] Selfmonitoring of a desired behavior is a core component of self-regulation as it precedes and supports one's ability to evaluate whether progress has been made toward an intended goal. 61,62 It requires deliberate attention to a behavior and the details of that behavior with documentation of these details over time. Research suggests that consistent self-monitors exercise more often, report less barriers to exercise, and achieve greater weight loss over time compared to those who do not engage in consistent self-monitoring of exercise.…”
Section: Goal-settingmentioning
confidence: 99%
“…Research suggests that consistent self-monitors exercise more often, report less barriers to exercise, and achieve greater weight loss over time compared to those who do not engage in consistent self-monitoring of exercise. 58,62 To increase adherence, self-monitoring should be limited to a single desired behavior associated with a well-defined goal. In addition, given the preference of AYAs for technology-based interventions, the use of smart devices (eg, phones, tablets, watches) may be a desirable method for tracking exercise and increasing adherence to exercise programs.…”
Section: Goal-settingmentioning
confidence: 99%